2021
DOI: 10.3390/brainsci11081015
|View full text |Cite
|
Sign up to set email alerts
|

Neural Alterations in Interpersonal Distance (IPD) Cognition and Its Correlation with IPD Behavior: A Systematic Review

Abstract: Background. Interpersonal distance (IPD) plays a critical role in a human being’s social life, especially during interpersonal interaction, and IPD is non-verbal social information and not only provides silent cues but also provides a secure space for personal relationships. IPD has been a research field of neural studies from the recent decade, researches had provided behavior and neural correlates of IPD. Objectives. This review aims to summarize the experimental paradigms of IPD-neural research, to reveal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…The current study suggested that the participants maintained the largest IPD when they faced an unvaccinated confederate, while the closest distance was found when they faced a confederate who had received a booster shot. This result is consistent with the self‐defence nature of IPD (Huang & Izumi, 2021 ; Ruggiero et al, 2017 ). When they faced an unvaccinated confederate, the participants were concerned that the confederate was unsafe and at risk of carrying the virus, leading to quite a large social distance.…”
Section: Discussionsupporting
confidence: 88%
“…The current study suggested that the participants maintained the largest IPD when they faced an unvaccinated confederate, while the closest distance was found when they faced a confederate who had received a booster shot. This result is consistent with the self‐defence nature of IPD (Huang & Izumi, 2021 ; Ruggiero et al, 2017 ). When they faced an unvaccinated confederate, the participants were concerned that the confederate was unsafe and at risk of carrying the virus, leading to quite a large social distance.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, even though the effect of visual contact on IMS appeared to be stronger when participants were closer, we found no evidence of a significant interaction. Provided that a relationship between interpersonal spatial proximity and social behavior is to be expected given previous research, 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 we might not have observed it because of two possible reasons. Either the effect of interpersonal spatial proximity was mitigated by other changing variables that we did not measure such as, for instance, attentional focus (see e.g., 76 , 80 , 81 , 82 ), or we might conclude that such relationship does not necessarily manifest in terms of IMS.…”
Section: Discussionmentioning
confidence: 89%
“…Functional brain-imaging studies revealed a different pattern of brain activity and connectivity in ASD and neurotypical individuals when measuring IPD (Massaccesi et al, 2021; Perry et al, 2015). In neurotypical people, activation of the dorsal intraparietal sulcus (DIPS), prefrontal and orbitofrontal cortices, ventral premotor and somatosensory cortices, and amygdala may play a role in IPD regulation during computerized versions of the stop-distance paradigm (in which participants are instructed to stop or tell the experimenter to stop at a preferred distance) and comfortable IPD task (in which participants are instructed to indicate the most comfortable distance as someone approaches them from the perimeter of a circle; Huang & Izumi, 2021). In addition to neural activity, functional connectivity was measured.…”
Section: Neurobiology and Neurodevelopment Of Distance Regulationmentioning
confidence: 99%